Cassandra High Performance Cookbook - Capriolo, Edward (Packt Publishing, 2011)
This is a cookbook and all tasks are approached as recipes. A recipe describes a task and outlines the steps necessary to complete this task. Some recipes in the book are examples of writing code. An example of this is a recipe that stores and accesses the entries of a phone book in Cassandra. The recipe consists of a description of the program, a full code example is given, the example is run, the output is displayed, and finally the how it works section describes the process or code in greater detail. Other recipes in the book describe a task. An example of this is a recipe that takes a snapshot back up of data in Cassandra. This recipe contains a description of the process, it then shows how to run the snapshot command and confirm that it worked, it then explains what the snapshot command does behind the scenes, finally the ‘see also’ section references other related recipes such as the recipe to restore a snapshot. This book is designed for administrators, developers, and data architects who are interested in Apache Cassandra for redundant, highly performing, and scalable data storage. Typically these users should have experience working with a database technology, multiple node computer clusters, and high availability solutions.